Medical imaging as a taphonomic tool: The naturally-mummified bodies from Takarkori rock shelter (Tadrart Acacus, SW Libya, 6100-5600 uncal BP). Issue 2 (22nd October 2019) - Profico, Antonio; Tafuri, Mary Anne; Di Vincenzo, Fabio; Ricci, Francesca; Ottini, Laura; Ventura, Luca; Fornaciari, Gino; Di Lernia, Savino; Manzi, Giorgio
Abstract : Purpose: Medical imaging applied to archaeological human remains represents a powerful tool for the study of specimens of exceptionally fragile nature. Here, the authors report a tomographic computerized investigation on the naturally mummified human remains from the Takarkori rock shelter (Libyan Sahara), dated to the Middle Pastoral Neolithic (ca. 6100-5600 uncal BP). The paper aims to discuss this issue. Design/methodology/approach: Medical radiological techniques allowed us to discriminate and isolate the tissues preserved thanks to their different electron density, driving us to detailed examinations of features of interest. Findings: With a focus on anatomy and taphonomy, the authors infer on post-depositional phenomena in a way that could not be achieved through traditional approaches. Originality/value: The investigation of digital data allows to acquire new sets of information with no risk for the original object. This case study is especially important considering that the human remains from Takarkori are currently not available to the scientific community due to political instability in Lybia.